IN VITRO POTENTIAL OF A-AMYLASE ENZYME INHIBITION OF A COMBINATION OF ETHANOL EXTRACT OF YAKON POTATO LEAVES (SMALLANTHUS SONCHIFOLIUS) AND KARAS TULANG ROOTS (CHLORANTHUS ERECTUS) AND ITS PHYTOCHEMICAL SCREENING - Haryoto Haryoto; Dinda Nurochmah Mujiyati; Agustono Wibowo (Journal of World Future Medicine, Health and Nursing, 2026)
Inhibiting carbohydrate-digesting enzymes such ?-amylase may help regulate type 2 diabetes mellitus, a long-term metabolic condition marked by continuous high blood sugar levels. The purpose of this research was to examine the phytochemical composition and in vitro ?-amylase inhibitory action of a mixture of yacon leaf (Smallanthus sonchifolius) and karas tulang root (Chloranthus erectus) ethanolic extracts. The plant materials were macerated in 70% ethanol to remove their constituent parts, and then the two extracts were mixed in a weight-for-weight ratio of 1:1. The DNS technique was used to assess the ?-amylase inhibitory activity, with acarbose as the positive control, and thin-layer chromatography was used for phytochemical screening. The yield of yacon leaves was 14.2% and that of karas tulang roots was 11.4% when extracted. There were terpenoids, polyphenols, alkaloids, flavonoids, and polyphenols found in the phytochemical screening. The combined extract exhibited an increase in ?-amylase inhibition ratio of 34.528 percent at 20 ppm to 90.359 percent at 200 ppm, which was concentration dependant. The combined extract had an IC?? value of 63.298 ± 0.162 ppm, while acarbose had an IC?? value of 43.183 ± 1.335 ppm. The inhibitory action of the combined extract was encouraging, even if it was not as strong as acarbose. These results indicate that a possible natural antidiabetic candidate might be created by combining yacon leaves and karas tulang roots via ?-amylase inhibition..